2018
DOI: 10.1155/2018/7571363
|View full text |Cite
|
Sign up to set email alerts
|

Plants and Their Bioactive Constituents in Mesenchymal Stem Cell-Based Periodontal Regeneration: A Novel Prospective

Abstract: Periodontitis is a common chronic inflammatory disease, which causes the destruction of both the soft and mineralized tissues. However, current treatments such as bone graft materials, barrier membranes, and protein products all have difficulties in regenerating the complete periodontal tissue structure. Stem cell-based tissue engineering has now emerged as one of the most effective treatments for the patients suffering from periodontal diseases. Plants not only can be substrates for life processes, but also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 135 publications
0
27
0
Order By: Relevance
“…As reviewed (Udalamaththa et al, 2016), several types of MSCs treated with individual or mixtures of herbal extracts, as well as with their purified compounds have resulted in increased proliferation, cell attachment and delayed senescence. These effects may vary due to cell type, inoculation number, culture conditions and product concentration (Xue et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…As reviewed (Udalamaththa et al, 2016), several types of MSCs treated with individual or mixtures of herbal extracts, as well as with their purified compounds have resulted in increased proliferation, cell attachment and delayed senescence. These effects may vary due to cell type, inoculation number, culture conditions and product concentration (Xue et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that plant-derived extracts and their natural compounds have demonstrated high activity in the management of wounds for different targets, such as suppressing the production of pro-inflammatory cytokines, reducing oxidative factors and enhancing anti-oxidative enzymes, and promoting neovascularization and angiogenic pathways [ 79 ]. Moreover, a number of preclinical studies have revealed that products extracted from plants can be successfully applied in modulating proliferation and differentiation of mesenchymal stem cells [ 80 ]. Furthermore, in the field of tissue engineering, plant-derived compounds or plant extracts can be incorporated into biomaterials to achieve their controlled release or used as biomaterials for cell transplantation [ 80 , 81 ].…”
Section: Physicochemical and Biological Properties Of Pdnvsmentioning
confidence: 99%
“…Moreover, a number of preclinical studies have revealed that products extracted from plants can be successfully applied in modulating proliferation and differentiation of mesenchymal stem cells [ 80 ]. Furthermore, in the field of tissue engineering, plant-derived compounds or plant extracts can be incorporated into biomaterials to achieve their controlled release or used as biomaterials for cell transplantation [ 80 , 81 ].…”
Section: Physicochemical and Biological Properties Of Pdnvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and preclinical studies have attempted to demonstrate the positive effects of plant compounds on bone matrix formation and cellular activity [14, 15]. However, this proposition is not always confirmed, mainly due to the great methodological variations involving the extract preparation, therapeutic schemes, and mechanisms of action [16].…”
Section: Introductionmentioning
confidence: 99%